Ice Cream Rounds: The implementation of peer support debriefing sessions at a Canadian medical school - Hiranandani, Rashi; Calder-Sprackman, Samantha (Canadian Medical Education Journal, 2020)
Wellness programs exist for medical students but the opportunity to debrief challenging experiences is lacking. We piloted Ice Cream Rounds (ICRs) for University of Ottawa clerkship students during the 2018-2019 academic year to provide students a safe environment to discuss challenges. Students reported a decrease in stress, anxiety and burnout, and an improvement in collegiality as a result of ICRs. ICRs could benefit medical students at other universities. To successfully implement ICRs at your institution, we recommend obtaining funding for ice cream, having peer facilitators, and creating a safe and confidential environment where students feel comfortable to debrief challenging experiences.